Pengaruh suhu penyimpanan terhadap kedalaman pengerasan dan kekuatan resin komposit - Kholidina Imanda Harahap (Intisari Sains Medis, 2018)
Introduction: Temperature plays a role in polymerization process of composite resin. Depth of cure is often used as a marker of polymerization adequacy in composite resins. Adequate polymerization will increase the mechanical properties of composite resin. The aim of this study was to evaluate the effect of storage temperature on depth of cure and compressive strength of composite resin. Method: Samples were made from nanofiller composite resin (Filtek Z350 XT,3M,ESPE,USA) after the materials were stored at 4°C and 24°C for two weeks. Twenty samples of nanofiller composite resins for each test group were prepared using metal mould with 6 mm in diameter and 4 mm thick.  Samples were cured under visible blue light for 20 second. The polymerized composite resin was measured for determining the depth of cure. Compressive strength of samples was tested by using Universal Testing Machine. Result: The results showed that depth of cure value of 24°C (3.90 ± 0.07 mm) was higher than 4°C (3.83 ± 0.17 mm) and compressive strength of 24°C (35.20 ± 4.63 MPa) was higher than 4°C (26.47 ± 3.13 MPa). Statistical analysis showed that depth of cure were no siginificant differences (p > 0.05) but in compressive strength were significant differences between test groups (p < 0.05). Conclusion: Storage temperature can affect the depth of cure and compressive strength of composite resin, although no significant difference on the depth of cure.